2008
DOI: 10.1097/acm.0b013e31816bdb96
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Medical School Deans: An Uncommon Problem

Abstract: Despite having an "extreme" job, only 2% of deans exhibited high levels of burnout. A high sense of control and self-efficacy, a supportive family, increasing length of service, and increasing age may be factors which reduce burnout in deans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…In addition, 27.0 % of respondents reported emotional exhaustion, 10.4 % reported depersonalization, and 28.7 % reported overall burnout. These rates compared very favorably to national rates among medical students 1 (37.4 %, 27.9 %, and 49.6 %, respectively, each p<0.001), internal medicine residents 2 (45.8 %, 28.9 %, and 51.5 %, respectively, each p<0.001), practicing physicians 3 (37.9 %, 29.4 %, and 45.4 %, respectively, each p<0.001), clerkship directors 4 (46.2 %, 41.3 %, and 61.8 %, respectively, p=0.002, p<0.001, and p<0.001, respectively) and medical school deans 5 (40.4 %, 23.6 %, and 47.2 %, respectively, p=0.02, p=0.002, and p=0.002, respectively) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 27.0 % of respondents reported emotional exhaustion, 10.4 % reported depersonalization, and 28.7 % reported overall burnout. These rates compared very favorably to national rates among medical students 1 (37.4 %, 27.9 %, and 49.6 %, respectively, each p<0.001), internal medicine residents 2 (45.8 %, 28.9 %, and 51.5 %, respectively, each p<0.001), practicing physicians 3 (37.9 %, 29.4 %, and 45.4 %, respectively, each p<0.001), clerkship directors 4 (46.2 %, 41.3 %, and 61.8 %, respectively, p=0.002, p<0.001, and p<0.001, respectively) and medical school deans 5 (40.4 %, 23.6 %, and 47.2 %, respectively, p=0.02, p=0.002, and p=0.002, respectively) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…2 In a recent national study of practicing physicians, burnout was reported in 45.4 %, symptoms of depression in 37.8 %, suicidal ideation in the prior 12 months in 6.4 %, and dissatisfaction with work-life balance in 37.1 %. 3 Similar issues have been reported to affect educational leaders, including internal medicine clerkship directors 4 and medical school deans, 5 among whom burnout rates of 61.8 % and 47.2 %, respectively, have been reported. Among internal medicine program directors, high rates of job turnover and dissatisfaction have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…The most obvious outcome of this would be higher levels of turnover, seen, for example, in a survey of medical school deans, 33 per cent of whom reported they would step down in the next two years (Gabbe, 2008), and amongst PhD students, where dropout levels can be as high as 30-50 per cent (Stubb et al 2012). However, signs can also be manifested as negative attitudes in the workplace and counterproductive workplace behaviours such as cynicism, incivility and sabotage (Kinman & Jones, 2001;Spector et al 2005).…”
Section: Outcomes Related To Poor Mental Health and Wellbeing For Indmentioning
confidence: 99%
“…Finally, several studies (Padilla & Thompson, 2016;Mauno et al 2014;Navarro et al 2010;Shanafelt et al 2009;Gabbe, 2008) use the Maslach Burnout Inventory (MBI) (Maslach & Jackson, 1981), a set of questions intended to capture burnout, defined as a prolonged response to chronic emotional and interpersonal job stressors. In this approach, burnout is characterised as consisting of three dimensions: emotional exhaustion, cynicism and inefficacy or reduced personal accomplishment (Maslach & Jackson 1981;Maslach et al 1996;Maslach et al 2001).…”
Section:  Limitations Of the Evidence Base In Generalmentioning
confidence: 99%
“…Cynicism (or depersonalization) refers to indifference or distant attitudes towards work, and reduced efficacy (or personal accomplishment) refers to a feeling of incompetence or lack of achievement and productivity at work 1,2) . Surveys have reported the prevalence of burnout as 2.5-51.1% in the health care sector [3][4][5] , 2-34% in the education sector 6,7) , 51.4% in the justice sector 8) , and 3-39% in the forest industry 9) . Burnout has significant consequences for employees, in forms such as anxiety, depression, sleep disturbances, headache, gastrointestinal illness, hypertension, muscle tension, chronic fatigue, and poor job performance.…”
mentioning
confidence: 99%